Bioseguridad en la pandemia Covid-19: Estudio cualitativo sobre la praxis de enfermería en Ecuador 2020 - Salvatierra Avila, Linda Yovana; Gallegos Gallegos, Edith Marlene; Orellana Pelaez, Christel Alexandra; Apolo Guaman, Laura Antonella (My University, 2021)
According to the WHO, biosecurity, it is a set of standards and measures to protect the health of personnel, against biological, chemical and physical risks to which they are exposed in the performance of their duties. The COVID-19 pandemic represents a new challenge to public health due to the transmission mechanism of SARS-CoV-2, the hospital biosafety protocols and standards have been adjusted under strict protection measures for the personnel that make up the first line of care, nursing professionals. Based on the above, an analysis of the perspective regarding the biosafety protocol, personal protective equipment, care, self-care and fear of contagion by SARS-CoV-2 faced by nursing personnel working in the COVID-19 pandemic was carried out. . The research had a qualitative-phenomenological approach, made up of five volunteer nursing professional informants, the data was collected through recorded interviews, they were transcribed and analyzed in categories, thus constructing results and conclusion of the investigation. The interviews carried out with the nursing staff revealed concern regarding the availability of supplies for protection due to the shortage of personal protective equipment worldwide, the increase in purchasing power and the low production, this being a potential danger to physical health at the time of delivery. exposure to provide care for infected patients. Concluding that the availability or absence of PPE puts at stake even the quality of care that can be given to patients, demonstrating the importance of caring for someone who, at this crucial moment in the history of humanity, is offering up their own life to save, that of others.
Según la OMS, bioseguridad, es un conjunto de normas y medidas para proteger la salud del personal, frente a riesgos biológicos, químicos y físicos a los que está expuesto en el desempeño de sus funciones. La pandemia COVID-19 supone un nuevo reto a la salud pública debido al mecanismo de transmisión del SARS-CoV-2, los protocolos y normas de bioseguridad hospitalaria se han ajustados bajo medidas estrictas de protección para el personal que integran la primera línea de atención, los profesionales de enfermería. En base a lo expuesto se realizó un análisis de la perspectiva respecto al protocolo de bioseguridad, equipo de protección personal, cuidado, autocuidado y temor al contagio por SARS-CoV-2 que enfrenta el personal de enfermería que laboran en la pandemia COVID-19. La investigación tuvo un enfoque cualitativa-fenomenológica, conformada por cinco informantes voluntarios profesionales de enfermería, los datos se recolectaron por medio de entrevistas grabadas, éstas fueron transcritas y analizadas en categorías, construyendo así resultados y conclusión de la investigación. Las entrevistas realizadas al personal de enfermería revelaron preocupación respecto a la disponibilidad de insumos para protección y normas de bioseguridad ante el COVID-19, debido al desabastecimiento del equipo de protección personal a nivel mundial, el incremento adquisitivo y la baja producción, siendo esto un peligro potencial para la salud física al momento de la exposición para brindar los cuidados a los pacientes contagiados. Concluyendo que la disponibilidad o ausencia de EPP pone en juego incluso hasta la calidad de atención que se pueda otorgar a los pacientes, demostrando la importancia de cuidar a quien en este momento tan crucial de la historia de la humanidad, se encuentra ofrendando hasta su propia vida por salvar, la de los demás
Keywords: BIOSEGURIDAD; PANDEMIA; COVID-19; ENFERMERIA; PRAXIS